Corynebacterium striatum as an Unusual Case of Endocarditis in an Intravenous Drug User: Case Report and Review of the Literature. Issue 6 (November 2017) - Hosseini Dehkordi, Seyed Hamed; Lee, Shawn; Aponte, Johat; Stavropoulos, Christine
Abstract : Abstract: A 59-year-old man, with a history of intravenous drug use, was admitted for 1 week of intermittent fever after a year of recurrent bouts of cellulitis. He quickly defervesced on empiric antibiotic therapy. Admission blood cultures were positive for Corynebacterium striatum as were wound cultures, which also grew methicillin-resistant Staphylococcus aureus and coagulase-negative Staphylococcus . A holosystolic murmur was heard. His transthoracic echocardiogram showed mitral valve prolapse, regurgitation, and a flail leaflet. The transesophageal echocardiogram revealed small perforations and a vegetation of the mitral valve. The endocarditis was successfully treated with surgical repair of the mitral valve and 6 weeks of intravenous vancomycin. Corynebacterium striatum is an unusual cause of endocarditis. It should not be dismissed as a contaminant in patients with risk factors for endocarditis. Abstract : Corynebacterium striatum bacteremia should not be dismissed as a contaminant. A lack of previous nosocomial exposure should not exclude consideration of C. striatum as a community acquired etiologic agent for infective endocarditis in at risk patients. In our patient who used intravenous drugs, C. striatum was isolated from superficial wound, blood, and mitral valve tissue cultures. Treatment with vancomycin is recommended based on comparative minimum inhibitory concentrations of antibiotics tested against C. striatum .